UBE2T Promotes Temozolomide Resistance of Glioblastoma Through Regulating the Wnt/β-Catenin Signaling Pathway - Wang Y; Gao G; Wei X; Zhang Y; Yu J (Dove Medical Press, 2023)
Yang Wang, Ge Gao, Xiangpin Wei, Yang Zhang, Jian Yu Department of Neurosurgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People's Republic of ChinaCorrespondence: Jian Yu, Department of Neurosurgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Tel + 86 551 62283413, Fax + 86 551 62283413, Email yujianqi024@163.comPurpose: Patients with glioblastoma (GBM) have poor prognosis and limited therapeutic options, largely because of chemoresistance to temozolomide (TMZ) treatment. Ubiquitin conjugating enzyme E2 T (UBE2T) plays a key role in regulating the malignancy of various tumors, including GBM; however, its role in TMZ resistance of GBM has not been elucidated. The purpose of this study was to clarify the role of UBE2T in mediating TMZ resistance and investigate the specific underlying mechanism.Methods: Western blotting was used to detect the protein levels of UBE2T and Wnt/β-catenin-related factors. CCK-8, flow cytometry, and colony formation assays were used to examine the effect of UBE2T on TMZ resistance. Wnt/β-catenin signaling pathway activation was inhibited using XAV-939, and a xenograft mouse model was generated to clarify the function of TMZ in vivo.Results: UBE2T knockdown sensitized GBM cells to TMZ treatment, whereas UBE2T overexpression promoted TMZ resistance. The specific UBE2T inhibitor, M435-1279, increased the sensitivity of GBM cells to TMZ. Mechanistically, our results demonstrated that UBE2T induces β-catenin nuclear translocation and increases the protein levels of downstream molecules, including survivin and c-Myc. Inhibition of Wnt/β-catenin signaling using XAV-939 blocked TMZ resistance due to UBE2T overexpression in GBM cells. In addition, UBE2T was shown to facilitate TMZ resistance by inducing Wnt/β-catenin signaling pathway activation in a mouse xenograft model. Combined treatment with TMZ and UBE2T inhibitor achieved superior tumor growth suppression relative to TMZ treatment alone.Conclusion: Our data reveal a novel role of UBE2T in mediating TMZ resistance of GBM cells via regulating Wnt/β-catenin signaling. These findings indicate that targeting UBE2T has promising potential to overcome TMZ resistance of GBM.Keywords: glioblastoma, temozolomide, drug resistance, UBE2T, Wnt/β-catenin